An antibody–drug conjugate active against antibiotic-resistant Neisseria gonorrhoeae - Hayley Lavender; Vincent Oliver; Daniel Lucy; Timothy A. Barendt; Ann E. Jerse; Christoph M. Tang (Proceedings of the National Academy of Sciences, 2026)
Neisseria gonorrhoeae is the causative agent of gonorrhea, a sexually transmitted infection which is rising in incidence, with increasing drug-resistant strains posing a significant public health threat. To address the urgent need for novel therapies, we developed an antibody–drug conjugate (ADC) that targets this important human pathogen. We utilized Tridecaptin A 1, a potent antimicrobial peptide (AMP) against Gram-negative bacteria that exhibits significant toxicity against human cells, limiting its development for clinical use. By conjugating the Tridecaptin A 1 analogue, Oct-TriA 1 to a monoclonal antibody (mAb) that specifically targets gonococcal MtrE, the outer membrane component of a drug efflux pump that is upregulated in resistant strains, we aim to selectively deliver the AMP to the gonococcus. However, Oct-TriA 1 was not bactericidal when directly conjugated to mAb. To circumvent this, we exploited an immune evasion mechanism employed by the gonococcus by introducing a linker between Oct-TriA 1 and the mAb which is specifically cleaved by the IgA protease (IgAP) secreted by the gonococcus; the IgAP inactivates human IgA. This ADC has no detectable toxicity for relevant human cells, kills the gonococcus in an MtrE- and IgAP-dependent manner, and is active against a strain which is resistant to first line agents. This modular ADC platform could be extended to other bacterial pathogens which employ proteases to evade immune killing, offering a strategy in the fight against antimicrobial resistance.